1958
DOI: 10.1063/1.1722954
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Motion in Polypropylene

Abstract: Molecular motion in polypropylene has been studied both by measurements of dynamic mechanical properties and by observations of nuclear magnetic resonance line shapes. The mechanical measurements were made in the audio-frequency region over the temperature range from 80°K to the melting point. Both completely amorphous and highly crystalline samples of polypropylene were investigated. In the amorphous sample, two transitions were observed, a broad but weak secondary one near 235°K and a relatively sharp primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…A transition at this temperature was reported earlier on the basis of results from mechanical relaxation and thermally stimulated current experiments. 4,7 Although this component also retains its solid character, changes in the magnitude of this fraction are well correlated with the temperature-induced transitions leading to the appearance of the fractions with higher mobilities (i.e., intermediate, semiliquid, and liquid; see The appearance of the intermediate component at Ϫ15°C (Figs. 2, 3 and 7) corresponds well to the glass-to-rubber transition (or lower glass transition) found in earlier investigations.…”
Section: Present Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transition at this temperature was reported earlier on the basis of results from mechanical relaxation and thermally stimulated current experiments. 4,7 Although this component also retains its solid character, changes in the magnitude of this fraction are well correlated with the temperature-induced transitions leading to the appearance of the fractions with higher mobilities (i.e., intermediate, semiliquid, and liquid; see The appearance of the intermediate component at Ϫ15°C (Figs. 2, 3 and 7) corresponds well to the glass-to-rubber transition (or lower glass transition) found in earlier investigations.…”
Section: Present Resultsmentioning
confidence: 99%
“…In addition, a phase transition at about Ϫ40°C occurs in the solid, amorphous phase. 4,7 In the crystalline phase, a double premelting transition at ϳ80 and ϳ110°C have been reported. 4 The molecular mechanisms responsible for the transitions in the crystalline phase of isotactic polypropylene were recently investigated with 2D exchange NMR.…”
Section: Review Of Phases Observed In Isotactic Polypropylenementioning
confidence: 99%
“…Kindl and Reiter24 suggested that, below glass‐transition temperature T g , already existing open spaces, which at times are blocked by local motions, are getting suitable for the formation of Ps. Isotactic PP is known to exhibit typically two glass transitions 25–29. The upper and the lower glass‐transition temperatures have been interpreted as arising from the onset of the molecular motions in the amorphous regions under the constraint imposed by the crystalline regions and those in the regions free from the constraint, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The reflection of the stereochemical structure in NMR spectra and the effect of stereo regularity on the relaxation time of polymers in bulk have been examined in a series of studies, in which the subjects for the investigation were polyacrylates [13,14,507,574], polypropylene [334,407,600,602,644], and other polymers.…”
Section: IIImentioning
confidence: 99%
“…Sauer et al [600] found that the fall in 6.R~, corresponding to the f3 transition (glass transition in amorphous regions) in isotactic polypropylene occurs at temperatures which are approximately 30° higher than in atactic polymer.…”
Section: IIImentioning
confidence: 99%